2022
DOI: 10.1063/5.0109206
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient detection of a single photon with hole-patterned superconductor microstrips

Abstract: In this Letter, we report on pattern engineering in superconducting microstrips to achieve a fast and efficient detection of a single-photon over a large detection area. The proposed detector is composed of hole-patterned superconductor microstrips fabricated with a 5-nm-thick amorphous molybdenum silicide film. It exhibits a saturated internal detection efficiency at 1550 nm with a negligible dark count rate and a recovery time of 9 ns with a large detection area (50 × 50 μm2). The simulation reveals that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…To summarise, we investigated the properties of a superconducting microwire pinhole meander, showing single-photon detection and dark-count properties that are significantly different from those of normal microwire meander detectors [14][15][16]24]. This pinhole meander exhibits a robust critical current against magnetic field within a certain magnetic-field window spanning ≈±16 mT [25,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarise, we investigated the properties of a superconducting microwire pinhole meander, showing single-photon detection and dark-count properties that are significantly different from those of normal microwire meander detectors [14][15][16]24]. This pinhole meander exhibits a robust critical current against magnetic field within a certain magnetic-field window spanning ≈±16 mT [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that defects, such as artificial holes, can trap vortices and hinder their motion, thereby increasing the current-carrying capability of a superconducting film [19][20][21][22][23]. This phenomenon can be used for changing the properties of superconducting microwires and detectors [24]. The effect of a single hole on the critical current of a NbN-based microbridge was recently investigated, and corresponding experiments showed that the application of an external magnetic field B has only a weak effect on the critical current I c , leading to a plateau in I c (B).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Xu et al reported that an NbN SMSPD irradiated using helium ions achieved nearsaturation detection at a wavelength of 1550 nm, with an SDE exceeding 90% [17]. Furthermore, numerous novel findings were raised in the field of SMSPDs, such as those related to materials [18], geometric layout design [19,20], and optical lithography fabrication [18,21,22].…”
Section: Introductionmentioning
confidence: 99%